2008
DOI: 10.2322/tjsass.51.133
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis on the Emission of Light from Methane-Air Lean Premixed Flames: Diagnostics of the Flame Instability

Abstract: This paper deals with time series analysis on the emission of light from methane-air lean premixed flames. Planar flames formed on a flat burner at the equivalence ratio of unity; cellular flames formed at low equivalence ratios, because diffusive-thermal effects have a destabilizing impact in this range. We measured the light emission to get time series of intensity, and obtained the root mean square (RMS) and power spectrum density of the emission intensity normalized by its average value. The RMS increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In the field of combustion science and physics, nonlinear time series analysis has been applied to the study of dynamic motion in a thermal pulse combustor, 10,11 detonation, 12 and cellar flames. 13 in recent years. Regarding the instability of swirling flames, the suitability of nonlinear time series analysis for characterizing the dynamic behavior of an unstable fluctuating flame front was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of combustion science and physics, nonlinear time series analysis has been applied to the study of dynamic motion in a thermal pulse combustor, 10,11 detonation, 12 and cellar flames. 13 in recent years. Regarding the instability of swirling flames, the suitability of nonlinear time series analysis for characterizing the dynamic behavior of an unstable fluctuating flame front was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…By performing FFT on the time series, he showed that the peak frequency is also lower at low equivalence ratios. This peak frequency is the same as the general frequency of premixed flames, mainly due to the shear current between hot burned gases and atmospheric gases 7 .…”
Section: Introductionmentioning
confidence: 58%
“…5 ). This range is included in similar articles, such as those by Kadovaki et al 7 .
Figure 5 Spectral power diagram of a photodiode with an equivalence ratio of 0.79 and a heat capacity of 12.77 kW.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses on the combustion of biogas because of wide applications in Thailand. In the past, the combustion of low-carbon fuel such as methane/air, butane/propane/air, and hydrogen/air [3][4][5] were investigated. In order to reduce the emission, the lean combustion was studied and found the effects of air/fuel ratio owing by thermal-diffusive instability [6][7].…”
Section: Introductionmentioning
confidence: 99%